Inside the leader's mind : five ways to think like a leader - Mellon, Elizabeth (Financial Times Prentice Hall, 2011)
Inside the Leader's Mind reveals the five common ways effective leaders think and gives you the tools you need to evolve your thinking and become a better leader. Drawn from the collective wisdom of 20 world-class leaders, Inside the Leader's Mind shows you how to think your way to the very top. Practical and straightforward, Inside the Leader's Mind will show you how to think differently so you can become a world-class leader.